Administrative legacy of ancient India in relation to modern public administration - Subramaniam, V. (1996)
Exploring the linkage between ancient Indian administrative legacy and modern public administration, the author first traces the evolution of tantacular imperial bureaucracy in India about 400 BC with its socio-economic context as evidenced in Kautilya's Arthasastra and Asokan inscriptions. He then analyses how and why imperial unity through conquests and bureaucratisation failed in India due to lack of collusion between literati and rulers (which did establish in China through neo-Confucian synthesis) and how diluted administrative practices interlaced with feudalism were transmitted to India through centuries of political division and foreign conquests. It is followed by a discussion on how the institution of district overlord coordinator, main remnant of Indian administrative tradition, was modernised by East India Company for export to British Afro-Asian colonies. Concluding with a critical look on Marxist and Weberian attitudes to Pre-British bureaucracies in India, he suggests a fresh look on these sans Weberian and Marxian commitments. - Reproduced
Keywords: Public administration - India; Public administration